Old-age Pension Systems: A Theoretical Evaluation - Stefan Homburg (Reforming the Welfare State, 1997)
The paper evaluates the theoretical literature on public pension schemes. First, the terms pay-as-you-go and capital reserve are made precise. These two systems are then compared, followed by a consideration of their efficiency properties. Thereafter conversion policies are discussed. – – Der Artikel bewertet die theoretische Literatur zur Gesetzlichen Rentenversicherung. Er vergleicht das Umlageverfahren und das Kapitaldeckungsverfahren, betrachtet deren Effizienzeigenschaften und diskutiert die Möglichkeit der Umwandlung eines Umlageverfahrens in ein Kapitaldeckungsverfahren.
Keywords: H55; 330; Pay-as-you-go; Public pensions; Umlageverfahren; Rentenversicherung